All Days 2012
DOI: 10.2118/154142-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Water Flooding Experiments and Interpretation by Simulations

Abstract: Even though the proposed screening criteria for low salinity water flooding (LSWF) are fulfilled, improve recovery is not always obtained. The LSWF mechanisms are therefore still discussed. The objective for the study was to describe the brine-rock interactions at high and low salinity. Reservoir core plugs were flooded either by formation water, sea water and low salinity waters in succession or by low salinity water directly from initial water saturations. Effluent samples were analyzed for ionic concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 9 publications
5
46
0
Order By: Relevance
“…Skrettingland et al (2010) reported no/very low additional oil recovery during LSWF. Slightly higher recovery in LSWF core flooding experiments was reported by Fjelde et al (2012), but the oil was produced during much longer production period in LSWF than in high salinity flood. Since one mechanism can not explain all the reported observations, the mechanisms for the improved oil recovery in LSWF are still discussed.…”
Section: Introductionmentioning
confidence: 70%
“…Skrettingland et al (2010) reported no/very low additional oil recovery during LSWF. Slightly higher recovery in LSWF core flooding experiments was reported by Fjelde et al (2012), but the oil was produced during much longer production period in LSWF than in high salinity flood. Since one mechanism can not explain all the reported observations, the mechanisms for the improved oil recovery in LSWF are still discussed.…”
Section: Introductionmentioning
confidence: 70%
“…The desired final wettability is also matter of debate. Some researchers reported that low salinity water flooding change the wettability into neutral state rather than water-wet state [8], [9]. Ashraf et al [4] pointed out same result.…”
Section: Wettability Effects and Its Alterationmentioning
confidence: 87%
“…Furthermore, there is direct evidence that wettability altered to more water-wet during low salinity water flooding [9], [10]. Accordingly, initial and final wettability's are key indices which have been evaluated.…”
Section: Wettability Effects and Its Alterationmentioning
confidence: 99%
“…(3) Expansion of the double layer to be as the dominant mechanism of oil recovery improvement (Nasralla and Nasr-El-Din 2012). The general agreement among researchers is that low salinity waterflooding cause reservoirs become more water-wet (Fjelde, Asen et al 2012, Nasralla and Nasr-El-Din 2012, Sohrabi and Emadi 2013, Shalabi, Sepehrnoori et al 2014.…”
Section: Introductionmentioning
confidence: 95%